An Analysis of the Influence of Physical Activity Level on Total Knee Arthroplasty Expectations, Satisfaction, and Outcomes: Increased Revision in Active Patients at Five to Ten Years. (19th September 2018) - Ponzio, Danielle Y.; Chiu, Yu-Fen; Salvatore, Anthony; Lee, Yuo-Yu; Lyman, Stephen; Windsor, Russell E.
Update: This article was updated on September 19, 2018, because of a previous error. On page 1546, in the section titled "Discussion, " the sentence that had read "Although a significant improvement was found in the vast majority of the inactive group, surprisingly, a majority of the active group (72.7%) reported a decrease in their activity levels below their baseline at 5 to 10 years postoperatively." now reads "Although a significant improvement was found in the vast majority of the inactive group, surprisingly, a majority of the active group (72.7%) reported no change or a decrease in their activity levels below their baseline at 5 to 10 years postoperatively." Background: Patients undergoing total knee arthroplasty expect pain relief, functional improvement, and a return to physical activity. The objective of this study was to determine the impact of patients' baseline physical activity level on preoperative expectations, postoperative satisfaction, and clinical outcomes in patients undergoing total knee arthroplasty. Methods: Using an institutional registry from 2007 to 2012, we retrospectively identified patients who underwent a unilateral primary total knee arthroplasty for osteoarthritis and completed a preoperative Lower Extremity Activity Scale (LEAS), a Hospital for Special Surgery Knee Replacement Expectations Survey (HSS-KRES), and a Knee injury and Osteoarthritis Outcome Score (KOOS) evaluation in addition to 2-year KOOS and satisfaction evaluations. Active patients were defined by an LEAS level of 13 to 18. Active patients (n = 1, 008) were matched to inactive patients (n = 1, 008) by age, sex, body mass index, and comorbidities. The cohorts were compared with regard to the association of expectations with KOOS and satisfaction, the change in LEAS level from baseline to 2 years, complications, and revision surgical procedures. Multivariable analyses identified predictors of satisfaction, KOOS, and revision surgical procedures. Results: Significantly more active patients (68.2%) expected to be back to normal with regard to the ability to exercise and participate in sports compared with inactive patients (55.5%; p < 0.0001). Although overall satisfaction was equivalent, active patients were more commonly very satisfied with regard to the ability to do recreational activities (67.2% compared with 57.7%; p = 0.001). There were no associations between expectations and satisfaction or outcomes. Only the inactive patient group improved in activity level at 2 years. At 2 years, 69.5% of the inactive patients and 27.3% of the active patients improved upon their baseline activity levels (p < 0.0001). Complications rates were similar. The revision rate was higher for active patients (3.2%) compared with inactive patients (1.6%) at 5 to 10 years postoperatively (p = 0.019). Conclusions: At 2 years following total knee arthroplasty, inactive patients improved from baseline activity levels and active patients did not. Active patients had an elevated revision risk. Therefore, active patients should be carefully counseled regarding total knee arthroplasty to give them an understanding of its limitations and the potential risk of future revision. Level of Evidence: PrognosticLevel III . See Instructions for Authors for a complete description of levels of evidence.